Physicochemical characterization of Sargassum polcystum C. Agardh and its activity against dinitrofluorobenzene-induced allergic contact dermatitis in mice - Irish Mhel C. Mitra; Ross D. Vasquez; Reginald B. Salonga; Mary Jho-Anne Corpuz (Universitas Islam Indonesia, 2020)
Background: Sargassum polycystum C. Agardh is brown seaweed abundant in the Philippines. Recent studies showed that it has an anti-inflammatory property. However, its efficacy against allergic contact dermatitis (ACD) has not yet been studied and there are no established data regarding its physicochemical properties yet.Objectives: The objectives of this study were to evaluate the topical efficacy of S. polycystum crude polysaccharide (Spcp) using dinitrofluorobenzene (DNFB)-induced ACD murine model and to conduct physicochemical characterization on Spcp.Methods: ACD was induced by sensitizing the BALB/c mice through topical application of 0.5% DNFB on the shaved ventral skin. Spcp (25%, 12.5%, 6.25% w/w) and standard drug (Betamethasone 0.10%) were topically applied on the right ear of the mice for seven days after sensitization and right after the challenge on the eighth day. Seven days after sensitization, the right ear was challenged with 0.2% DNFB. Ear thickness was measured at baseline and 24-hrs post-challenge using a dial thickness gauge. Physicochemical characterization was also performed.Results: The results showed that topical application of Spcp inhibited the swelling produced during 24-hrs post-challenge. The analysis revealed that the 25% Spcp exhibited a statistically significant effect and was comparable with the inhibitory effect of the standard drug, betamethasone (p<0.05). The physicochemical characterization showed that Spcp contains a notable amount of carbohydrates, sulfate, and protein.Conclusion: In conclusion, our results suggest that topically applied Spcp can be an effective natural product to treat allergic contact dermatitis. However, further investigations are required to understand the mechanisms involved.Keywords: allergic contact dermatitis, physicochemical, polysaccharide